1-Imidoalkylphosphonium salts with modulated Cα–P+ bond strength: synthesis and application as new active α-imidoalkylating agents - Adamek, Jakub; Mazurkiewicz, Roman; Węgrzyk, Anna; Erfurt, Karol (Beilstein Journal of Organic Chemistry, 2017)
An effective synthesis of the hitherto unknown 1-imidoalkylphosphonium salts has been developed in the reported study. The crucial step in the method included the decarboxylative α-methoxylation of N-phthaloyl- or N-succinylamino acids to the corresponding N-(1-methoxyalkyl)imides, followed by the displacement of the methoxy group by the triarylphosphonium group through melting of the imide derivative with triarylphosphonium tetrafluoroborate. The imidoalkylating properties of the obtained 1-imidoalkylphosphonium salts were tested using the Tscherniac–Einhorn-type reaction with aromatic hydrocarbons as a model reaction. It was found that the Cα–P+ bond strength can be considerably reduced and the imidoalkylation of arenes can be markedly facilitated using 1-imidoalkylphosphonium salts derived from triarylphosphines with electron-withdrawing substituents such as tris(m-chorophenyl)phosphine, tris(p-chlorophenyl)phosphine and tris[p-(trifluoromethyl)phenyl]phosphine. Microwave irradiation also considerably facilitates the cleavage of the highly polar Cα–P+ bond.
Keywords: N-(1-arylalkyl)imides; α-imidoalkylating agents; imidoalkylation reactions; 1-imidoalkylphosphonium salts; Tscherniac–Einhorn-type reaction